Management of pediatric acute leukemias relapse after hematopoietic cell transplantation - Tavares, Rita de Cássia Barbosa; Pelegrina, Polliany Roberta Dorini; Breviglieri, Carla Nolasco Monteiro; Rodrigues, Ana Luiza de Mello; Zamperlini, Gustavo; Martins de Sousa, Adriana; Horn, Patricia Regina Cavalcanti Barbosa; Darrigo Jr, Luiz Guilherme; Daudt, Liane (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Prevention is the best way to avoid relapse after hematopoietic cell transplantation (HCT). Immunomodulation can enhance graft-versus-leukemia effect and, if graft-versus-host disease (GVHD) is absent, prophylactic donor lymphocyte infusion (DLI) may be indicated for high-risk patients. Maintenance strategies with blinatumomab, inotuzumab, tyrosine kinase inhibitors, hypomethylating agents or venetoclax can be effective in reducing relapse rates. However, maintenance therapy response depends on individual toxicity and physician’s experience in handle with dose adjustments, undesirable drug interactions and complications. Preemptive approach guided by minimal residual disease (MRD) or mixed chimerism is fundamental to prevent hematologic relapse. Target agent or immunotherapy followed by DLI can be used, and if no response, low-dose chemotherapy can be added to reach disease control. After relapse, antigen-directed therapies with blinatumumab for CD19 ALL and inotuzumab for CD22 ALL are good options to induce MRD negativity and bridge to second HCT. Emerging therapies like daratumumab, immune checkpoint or menin inhibitors are promising but require validation. CAR-T cell therapy can provide a better chance of long-term survival if low leukemia burden and absence of GVHD. It is also effective in extramedullary disease, mainly in central nervous system relapse. Patients with B-cell aplasia loss after CAR T-cell therapy are second transplant candidates, as well as those with acute myeloid leukemia who respond to salvage therapy. Second HCT outcomes are better if relapse occurred ≥ 12 months after the first HCT. Strategies for expanding access to immunotherapy and target agents are crucial to improve long-term survival in these children.